Strategi Penguatan Performa UMKM melalui Digitalisasi Pemasaran dan Optimalisasi Media Sosial di Kelurahan Klangon Kecamatan Bojonegoro Kabupaten Bojonegoro Jawa Timur - Suryati Eko Putro; Wahyu Rochana; Dina Susiani; Totok Mardianto; Shindu Hargo Dedali; Agung Pribadhi; Agus Agus; Rukin Rukin; Muhammad Sujudi; Nyardi Nyardi (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving national economic growth and are the main pillars of the community's economy. However, challenges in the digital era require MSMEs to adapt quickly, especially in marketing aspects, which are increasingly shifting to the digital realm. This community service activity discussed strategies for strengthening MSME performance through marketing digitalization and optimizing social media as a means of promotion and interaction with consumers. The activity was held in Klangon Village, Bojonegoro District, Bojonegoro Regency, East Java. The method used in this activity was a qualitative descriptive approach combined with a literature study related to the use of digital technology to support MSME marketing strategies. The identification results showed that the use of digital platforms such as social media, marketplaces, and business websites can have a significant impact on increasing product visibility, marketing efficiency, and expanding market reach, both locally, regionally, and nationally. Optimizing social media not only functions as a promotional tool but also builds more intensive interactions with consumers. Through the presentation of relevant, creative, and interactive content, MSMEs are able to increase customer engagement and strengthen brand loyalty. The findings of this activity confirm that digital marketing integrated with digital communication strategies can strengthen the competitiveness of MSMEs amidst increasingly fierce market competition. However, challenges remain, including limited digital literacy, a lack of technical skills, and a lack of understanding of effective digital marketing strategies among MSMEs. Therefore, ongoing efforts are needed to improve digital literacy, provide technical training, provide intensive mentoring, and provide policy support from the government and relevant stakeholders.